2019
DOI: 10.1002/hep.30628
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Surgery in Patients With Idiopathic Noncirrhotic Portal Hypertension: A Multicenter Retrospective Study

Abstract: In patients with idiopathic noncirrhotic portal hypertension (INCPH), data on morbidity and mortality of abdominal surgery are scarce. We retrospectively analyzed the charts of patients with INCPH undergoing abdominal surgery within the Vascular Liver Disease Interest Group network. Forty‐four patients with biopsy‐proven INCPH were included. Twenty‐five (57%) patients had one or more extrahepatic conditions related to INCPH, and 16 (36%) had a history of ascites. Forty‐five procedures were performed, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
(128 reference statements)
1
14
0
Order By: Relevance
“…Furthermore, a recent retrospective study comparing 66 patient with TIPSS prior to abdominal surgery (predominantly colorectal surgery) to 68 patients without a TIPSS pre-surgery showed no differences in post-operative complications and mortality 109. A retrospective study of patients with idiopathic non-cirrhotic portal hypertension (INCPH) undergoing non-hepatic surgery did not find that portal decompressive procedures prior to surgery affected outcomes, although the sample size was small 110. A prospective study showed the value of HVPG in predicting outcomes in cirrhotic patients undergoing non-hepatic surgery, with no patient having HVPG <10 mmHg developing decompensation 111.…”
Section: Indications For Tipssmentioning
confidence: 99%
“…Furthermore, a recent retrospective study comparing 66 patient with TIPSS prior to abdominal surgery (predominantly colorectal surgery) to 68 patients without a TIPSS pre-surgery showed no differences in post-operative complications and mortality 109. A retrospective study of patients with idiopathic non-cirrhotic portal hypertension (INCPH) undergoing non-hepatic surgery did not find that portal decompressive procedures prior to surgery affected outcomes, although the sample size was small 110. A prospective study showed the value of HVPG in predicting outcomes in cirrhotic patients undergoing non-hepatic surgery, with no patient having HVPG <10 mmHg developing decompensation 111.…”
Section: Indications For Tipssmentioning
confidence: 99%
“…According to L R Elkief, et al, patients with Idiopathic Non-Cirrhotic Portal Hypertension (INCPH), performed retrospective analyses of patients with INCPH undergoing abdominal surgery [4]. X Chen, et al, reviewed revealed laparoscopic splenectomy and laparoscopic splenectomy with devascularization to be safe and effective in the setting of liver cirrhosis and portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the article by Elkrief et al reporting long‐term outcomes of abdominal surgery in patients with idiopathic noncirrhotic portal hypertension (INCPH) . In a subgroup analysis, the authors compared the outcome of patients who had (n = 33) or did not have (n = 10) a preemptive transjugular intrahepatic portosystemic shunt (TIPS), showing that TIPS before surgery had no significant impact on postoperative outcomes.…”
Section: Effect Size For the Comparison Of The Patients With/without mentioning
confidence: 99%